Islamic Consumer Ethics and Buying Behavior of Muslim Gen Z: The Influence of Service, Promotion, Price, and Product Quality - Munawaroh Munawaroh; Zainal Zawir Simon; Toto Heriyanto (SAN Scientific, 2026)
This study aims to analyze the influence of service quality, promotion, price perception, and product quality on McDonald's consumers' purchasing decisions in Jakarta, and to assess these marketing factors from an Islamic economic perspective. This research employs an exploratory quantitative approach and a purposive sampling technique. A total of 135 respondents participated through questionnaire-based surveys. The data were analyzed using multiple linear regression. The results indicate that service quality, promotion, and product quality each have a positive and significant effect on purchasing decisions. In contrast, price perception has a significant, adverse effect, suggesting consumer sensitivity to pricing at fast-food outlets. Simultaneously, all independent variables significantly influence purchasing decisions. From an Islamic perspective, the findings reflect the principles emphasized by Imam Al-Qurthubi on fairness, transparency, and the provision of ethical values in market transactions, suggesting that marketing practices should align with Sharia-compliant consumer ethics. This study contributes to strengthening the understanding of Muslim consumer behavior and highlights the importance of integrating Islamic moral values in fast-food industry marketing strategies.